A new species of Moenkhausia from the rio Amazonas and rio Orinoco basins (Characiformes: Characidae) - Marinho, Manoela M. F.; Langeani, Francisco [UNESP] (Magnolia Press, 2010)
A new species of Moenkhausia is described from the rio Amazonas and rio Orinoco basins. The new species can be distinguished from congeners mainly by the combination of a conspicuous, relatively small and circular humeral spot, a black spot on the upper caudal-fin lobe, lower caudal-fin lobe without spot or a faint one, and middle caudal-fin rays hyaline or with dark tips. Mature males have a unique combination of two large-sized bony hooks on the anal-fin rays and tiny spines on the distal portion of all fins, which distinguishes the new species from any other species of Characidae.
Keywords: Systematics; Moenkhausia lepidura species-group; bony hooks